A case of knuckle pad syndrome in a middle‐aged man - Zachary Chandler; Kimberly Seamon; Karishma Ramsubeik; Gurjit Kaeley (Clinical Case Reports, 2022)
Abstract Knuckle pads are benign papules, nodules, or plaques overlying joints and typically manifest at the proximal interphalangeal joints (PIPs). They may be confused with other dermatologic or rheumatologic diseases. Treatment options for primary knuckle pads are limited and acquired knuckle pads typically improve with withdrawal of the offending insult.